Βελτιστοποίηση των δυναμικών χαρακτηριστικών ενός σασί gokart με τη βοήθεια ανάλυσης ιδιόμορφων και πεπαρασμένων στοιχείων - Κουλέρμου, Ανδρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The objective of this dissertation was to study a go-kart chassis, provided by a Cypriot Manufacturing Company, to improve its dynamic characteristics and suggest new improved modified design.The method of experimental modal analysis was first used to identify the actual dynamic characteristics like natural frequencies and mode shapes in the operating range of the go-kart engine, the main source of excitation frequencies (0-167 Hz = 0-10000rpm).The next step was a precise 3D AutoCAD modelling of the chassis and the input of the model in the Abaqus Finite Element software to modify and study the dynamics of the new chassis.A great effort was made to correlate and update the finite element Modal Analysis results to agree with the experimental.Emphasis was given in avoiding errors during both, the experimental and the Finite Element Analysis (FEA) phases of the project, with very good results.Using the FEA software, a number of new modified, improved models have been developed, shifting two out of the four troublesome natural frequencies out of the engine's operating range.Four new possible designs have been presented with improved operating range free of annoying natural frequencies.Using further FEA analysis the dynamic response of the four new chassis, to a known force, was tested, giving us the opportunity to indicate the best solution out of the four.Finally a study on engine mount isolators was presented giving a further reduction on the effect of the engine vibrations on the lower part of the frequency range.
Keywords: Gokart chassis; AutoCAD; Σασί gokart; AutoCAD